Updike's Creative So(u)rcery in Gertrude and Claudius. Issue 1 (1st January 2018) - Geckle, George L.
ABSTRACT: In John Updike's Gertrude and Claudius we have the uncommon example of a novelist spelling out for his readers in both a Foreword and an Afterword the sources that he used for his work, in this case an interpretation of the legendary Hamlet story. Although several critics have commented on some of Updike's references, no one has fully examined the way in which his acknowledged study of Shakespeare criticism and Hamlet films influenced him to the extent that he felt comfortable turning the Hamlet story—as we best know it from Shakespeare's play—upside down and making it into a paean to medieval adultery. I will examine all of the items mentioned in the Foreword and Afterword of his novel that clearly influenced Updike, but also suggest some unmentioned sources that probably influenced him.